Content-specific phenomenological similarity between episodic memory and simulation. Issue 3 (16th March 2019) - Thakral, Preston P.; Madore, Kevin P.; Schacter, Daniel L.
ABSTRACT: Numerous studies have indicated that remembering specific past experiences (i.e., episodic memory) and imagining specific novel future experiences (i.e., episodic simulation) are supported by common mental processes. An open question, however, is whether and to what extent the content of specific past episodes is sampled when simulating a specific future episode. The current study aimed to answer this question. Participants recalled past episodes each comprising two episodic details, a personally familiar location and person. Participants also simulated novel future episodes using recombined pairs of person and location details taken from different recalled episodes. Participants rated the vividness of each location and person in their memory and simulation. We conducted a multi-level analysis where the vividness rating during memory was used to predict the vividness rating during simulation at the level of individual shared details (i.e., location or person). The vividness of the memorial detail co-varied with the vividness of the simulated detail; this relationship persisted even after accounting for the underlying familiarity of the details. These findings strongly suggest that simulations of specific future experiences are based upon the contents of specific prior episodes.